2020
DOI: 10.1364/oe.388899
|View full text |Cite
|
Sign up to set email alerts
|

Weak and strong coupling of photons and excitons in planar meso-cavities

Abstract: The interaction of an exciton and cavity modes is considered in planar meso-cavities, which have lateral sizes corresponding to few wavelengths. In meso-cavities, the frequency interval between the optical modes is comparable or smaller than the value of the Rabi splitting between the exciton and the optical modes. The Hamiltonian of the interaction between the exciton and the cavity modes is constructed, and it is shown that such an interaction between the cavity modes and the exciton can occur both in weak a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…In the present research, we used an approach with some advantages regarding others similar reported in the literature, introducing meso-cavities coupled to well-studied PhC cavities to accomplish doubly resonance effects. Previous reports have shown that meso-cavities of different geometries can support strongly confined resonant modes with wavelengths tens of times smaller than the cavity characteristic dimensions [20]. Furthermore, meso-cavities can have high Q factors for a wide range of frequencies and thus, can be used to enhance quantum optical effects [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present research, we used an approach with some advantages regarding others similar reported in the literature, introducing meso-cavities coupled to well-studied PhC cavities to accomplish doubly resonance effects. Previous reports have shown that meso-cavities of different geometries can support strongly confined resonant modes with wavelengths tens of times smaller than the cavity characteristic dimensions [20]. Furthermore, meso-cavities can have high Q factors for a wide range of frequencies and thus, can be used to enhance quantum optical effects [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that meso-cavities of different geometries can support strongly confined resonant modes with wavelengths tens of times smaller than the cavity characteristic dimensions [20]. Furthermore, meso-cavities can have high Q factors for a wide range of frequencies and thus, can be used to enhance quantum optical effects [20]. Since the dimensions of the meso-cavities are very large compared to the wavelength of the resonant mode, it is possible to design a second microcavity within the main meso-cavity.…”
Section: Introductionmentioning
confidence: 99%
“…эксперимент, вырастить гораздо проще, чем структуры другой геометрии. Также в гексагональных структурах гораздо вероятнее появление одной высокодобротной моды, которая может эффективно взаимодействовать с экситоном[8].В первую очередь определим размеры гексагональной структуры, в которой реализуется такая структура мод, где высокодобротная мода будет иметь энергию, близкую к энергии экситона. Расчет собственных мод и их добротностей для двумерного гексагонального мезорезонатора проводился с помощью моделирования в COMSOL Multiphysics.…”
unclassified